2012
DOI: 10.1111/j.1651-2227.2012.02834.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcome of resective epilepsy surgery in Norwegian children

Abstract: The results of epilepsy surgery in this paediatric cohort are very edifying, and it is our impression that this treatment option is underused in Norway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…33 A recent Norwegian retrospective questionnaire study in children with a response rate of 70% reported 58% seizure-free after a mean of 7 years. 23 However, sustained seizure freedom was not reported in these studies.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…33 A recent Norwegian retrospective questionnaire study in children with a response rate of 70% reported 58% seizure-free after a mean of 7 years. 23 However, sustained seizure freedom was not reported in these studies.…”
Section: Discussionmentioning
confidence: 89%
“…A number of studies report cross-sectional long-term follow-up of pediatric epilepsy surgery, with seizure freedom in 50% to 82% of patients 5 to 12 years after TLR. 2328 Only one study is longitudinal and reports sustained seizure freedom (Engel 1) in 54% of patients 5 years after TLR. 29 …”
Section: Discussionmentioning
confidence: 99%
“…In most series improvement or resolution of epileptic encephalopathy is reflected in improved cognition and behavior, either formally tested or subjectively reported by the patient's family [ 95 ]. Cognitive and behavioral improvements after hemispherectomy have been noted since the onset of the application of the technique to epilepsy [ 96 , 97 ], even being credited for the resolution of Von Monakow's diaschisis [ 98 ].…”
Section: Childhood Syndromesmentioning
confidence: 99%
“…For selected patients, surgery with localization and resection of the epileptogenic lesion is the best alternative to achieve seizure freedom. Among pediatric cohorts, the rate of seizure freedom after surgery ranges from 40 to 82% [6-14]. Surgery is, however, a costly undertaking, and thus economic utility should be investigated.…”
Section: Introductionmentioning
confidence: 99%